1999
DOI: 10.1046/j.1471-4159.1999.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nurrl Expression Increases the Vulnerability of Mesencephalic Dopamine Neurons to MPTP‐Induced Injury

Abstract: Mutation in the Nurr1 gene, a member of the nuclear receptor superfamily, causes selective agenesis of dopaminergic neurons in the midbrain of null mice. Homozygous Nurr1 knockout mice (Nurr1Ϫ/Ϫ) die 1 day after birth, but heterozygous mice (Nurr1ϩ/Ϫ) survive postnatally without obvious locomotor deficits. Although adult Nurr1ϩ/Ϫ mice show significantly reduced Nurr1 protein levels in the substantia nigra (SN), they display a normal range of tyrosine hydroxylase-positive neuron numbers in the SN and normal lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Studies in Nurr1-deficient mice (±) indicate that the amount of Nurr1 is important to keep homeostasis during the life of dopamine neurons (Le et al, 1999; Jiang et al, 2005; Eells et al, 2006; Zhang et al, 2012). For instance, aged Nurr1 (±) mice have a significant decrease in rotarod performance and locomotor activity, a motor impairment analogous to Parkinson's disease associated with decreased dopamine levels in the striatum (Jiang et al, 2005).…”
Section: Nur Transcription Factors and Dopaminergic Transmissionmentioning
confidence: 99%
“…Studies in Nurr1-deficient mice (±) indicate that the amount of Nurr1 is important to keep homeostasis during the life of dopamine neurons (Le et al, 1999; Jiang et al, 2005; Eells et al, 2006; Zhang et al, 2012). For instance, aged Nurr1 (±) mice have a significant decrease in rotarod performance and locomotor activity, a motor impairment analogous to Parkinson's disease associated with decreased dopamine levels in the striatum (Jiang et al, 2005).…”
Section: Nur Transcription Factors and Dopaminergic Transmissionmentioning
confidence: 99%
“…However, MK-801 treatment in combination with l -DOPA in 6-OHDA lesioned rats increased the release of dopamine in lesioned striatum as compared to intact striatum, indicating that the effect of MK-801 on release of dopamine in striatum or SNpc depend upon the integrity of nigrostriatal pathway . The mesencephalic DAergic neurons with reduced Nurr-1 expression have been shown to be more vulnerable to MPTP-induced injury . Previous studies have shown that Nurr-1 and Pitx-3 are essentially involved in the long term survival and terminal differential of DAergic neurons , and the deficiency of Pitx-3 is reported to be responsible for the loss of TH expression in SNpc .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the expression of the positive genetic marker for DA neurons, tyrosine hydroxylase (TH), a rate-limiting enzyme in dopamine synthesis (Daadi and Weiss, 1999;Sonntag et al, 2004;Kirkeby et al, 2017a), and the levels of GIRK2 have also been observed in many cell types in vitro (Thompson et al, 2005;Kirkeby et al, 2012;Reyes et al, 2012;Grow et al, 2016). Moreover, common positive markers used to isolate high-quality DA progenitor cells include EN1 and SPRY1 (Simon et al, 2001;Alberi et al, 2004;Kirkeby et al, 2017a); Nurr1 (Le et al, 1999); FOXA2, LMX1B, and MSX1 (Andersson et al, 2006;Chung et al, 2011), and the bicoid-related homeodomain factor Ptx3/Pitx3 (Hargus et al, 2010). It is noteworthy that some discrepancies have been found with the requirement for the presence of floor plate-specific cell surface marker CORIN expression (Ono et al, 2007;Chung et al, 2011;Kriks et al, 2011;Kirkeby et al, 2012Kirkeby et al, , 2017aDoi et al, 2014;Arenas et al, 2015;Fan et al, 2020).…”
Section: Assessment Of the Efficacy Of Cell Transplants With Immunostmentioning
confidence: 99%